Student perception of Natural Resource Management regarding virtual methodological strategies for subjects with practical components during COVID-19 times (Revista Electrónica Calidad en la Educación Superior, 2023)
At the beginning of 2020, when the international health emergency was declared due to the COVID-19 disease, the transformation to virtuality at the Distance State University (UNED) of Costa Rica was less complex than in other higher education institutions. However, it was necessary to adapt subjects with practical in-person activities such as laboratories and field trips to a 100% virtual modality. In the Natural Resources Management (MARENA) program, specifically in the Natural Sciences (CN) and Ecology and Environmental Education (EEA) courses, methodological strategies were designed and implemented, including supporting audiovisual materials, video tutorials, at-home laboratory practices, virtual field trips, virtual oral presentations, and collaborative work. This research used a mixed qualitative and quantitative approach with descriptive and exploratory aspects. Additionally, a tool was applied to assess students' perception of the virtual methodological strategies in four MARENA subjects with practical components. It was determined that the 100% virtual education process caused by COVID-19 facilitated the maximization of virtual tools usage, the need for digital literacy among teachers and students, the continuous search for methodological strategies, the design of detailed instructions for students, and finally, the value of in-person fieldwork and laboratory activities compared to the virtual format became evident. The objective of this study is to analyze students' perception in the CN and EEA courses regarding the virtual methodological strategies applied in subjects with practical components during the pandemic in 2021.
Keywords: communication and information technologies (ICT); methodological strategies; practical activities; online learning; pandemic